The profile and frequency of known risk factors or comorbidities for deep vein thrombosis in an urban district hospital in KwaZulu-Natal - Damilola Awolesi; Mergan Naidoo; Mohammed H. Cassimijee (AOSIS, 2016)
Background: Although deep vein thrombosis (DVT) is a preventable disease, it increases the morbidity and mortality in hospitalised, patients, resulting in considerable economic health impact. The identification and primary prevention of risk factors using risk assessment and stratification with subsequent anti-thrombotic prophylaxis in moderate- to severe-risk categories is the most rational means of reducing morbidity and mortality. Aim and setting: The aim of the study was to describe the profile and frequency of known risk factors or comorbidities of hospitalised medical patients with ultrasound-diagnosed DVT in an urban district hospital in KwaZulu-Natal. Methods: A retrospective review of clinical notes of all medical patients (age ≥ 13 years) admitted to the hospital with ultrasound-diagnosed DVT between July and December 2013. Results: The median age was 40 years (interquartile range 32-60 years) and female preponderance was 72.84%. HIV and tuberculosis emerged as the prevalent risk factors, accounting for 51.85% and 35.80%, respectively. Other risk factors observed were recent hospitalisation (34.57%), smoking (25.93%), previous DVT (19.75%) and congestive cardiac failure (18.52%). Conclusion: DVT in our study occurred predominantly in young female patients unlike previous studies where patients were generally older. Furthermore, HIV and tuberculosis were the two most common known risk factors or comorbidities observed. Clinicians should have a heightened awareness of venous thromboembolism in patients with either condition or where both conditions occur together and appropriate thromboprophylaxis should be administered. Keywords: Deep Vein Thrombosis; risk factors; profile